The Impact of Working Mothers’ Bargaining Power on Their Children's Human Capital in Indonesia - Anggaraini, Ni Komang Widya; Setyari, Ni Putu Wiwin (Universitas Muhammadiyah Yogyakarta, 2020)
Education is one of the strongest instruments owned by society to reduce poverty and vulnerability. This is because knowledge and skills are acquired through education. Thus, increasing productivity and creating access to employment opportunities. So that income will increase along with the increase in education. The most strategic target in developing quality human resources is children. There is an empirical study of the effect on household resource allocation where household decisions are influenced by the power that individuals have in the household. The distribution of power within the household can affect the level of spending on education for each child.Â This study aims to determine the impact of working mothers on their children's human capital in Indonesia and the differences in the influence of relative education and the relative income of working mother on children's human capital in Indonesia. The analysis technique used is the Ordinary Least Square (OLS) and Chow-test to determine the difference in the effect of the relative education and relative income of working mothers on their children's human capital in Indonesia.Â Using IFLS5 data, we found out that the impact of working mothers has a significant effect on children's human capital in Indonesia and there is a significant difference where the income of working mothers has a greater influence on children's human capital in Indonesia.